Towards a Universal System for the Classification of Boiling Surfaces - Alexander Ustinov; Jovan Mitrovic; Dmitry Ustinov (Journal of Nuclear Engineering)
A lot of novel surface treatment technologies have appeared over the last few decades, offering great possibilities for practical use. Modified surfaces have confirmed their successful application in thermal engineering for boiling heat transfer enhancement and single-phase convection. Several classification approaches for boiling surfaces exist in the literature; however, a full, physically based, and commonly accepted universal system is still missing. This paper proposes such a classification system, based on considerations of physical mechanisms underlying the nucleation process and enhancement mechanism during different stages of vapor bubble growth. It also presents an overview of recent advances in the development of enhanced boiling surfaces.